Unsettled integration: Pre- and post-migration factors in Congolese refugee women's resettlement experiences in the United States. (November 2016) - Wachter, Karin; Heffron, Laurie Cook; Snyder, Susanna; Nsonwu, Maura Busch; Busch-Armendariz, Noël Bridget
By 2019, the United States plans to resettle approximately 50, 000 refugees from the Democratic Republic of the Congo. The purpose of this study was to identify and understand the challenges, risks, and strengths of adult Congolese refugee women resettled in the United States to help policymakers, service providers, and other stakeholders prepare for the arrival of Congolese women and their families. Researchers conducted in-depth interviews and focus groups with Congolese refugee women ( n = 28) and resettlement service providers ( n = 29) in three US cities. The findings of this study reveal the complex and dynamic nature of Congolese refugee women's resettlement experiences in the United States and highlight the importance of recognizing the intersection of pre- and post-migration factors during resettlement. This article offers concrete implications for the social work profession and practitioners.